Gitelman-Like Syndrome Caused by Pathogenic Variants in mtDNA. Issue 2 (February 2022) - Viering, Daan; Schlingmann, Karl P.; Hureaux, Marguerite; Nijenhuis, Tom; Mallett, Andrew; Chan, Melanie M.Y.; van Beek, André; van Eerde, Albertien M.; Coulibaly, Jean-Marie; Vallet, Marion; Decramer, Stéphane; Pelletier, Solenne; et al.
Significance Statement: Biallelic pathogenic variants in SLC12A3, encoding the thiazide-sensitive sodium chloride cotransporter NCC, cause Gitelman syndrome. Gitelman patients suffer from hypokalemic alkalosis, hypomagnesemia, and salt wasting. A subset of Gitelman syndrome cases remains genetically unsolved. This paper describes the identification of pathogenic mitochondrial DNA (mtDNA) variants in the genes encoding the transfer RNAs for phenylalanine ( MT-TF ) and isoleucine ( MT-TI ) in 13 families with a Gitelman-like phenotype. Six families were additionally affected by progressive CKD. Mitochondrial dysfunction was demonstrated in patient-derived fibroblasts and linked to defective sodium reabsorption by NCC in vitro. These findings advocate for screening for mtDNA variants in unexplained Gitelman syndrome patients and influence genetic counseling of affected families. Furthermore, they provide insight into the physiology of renal sodium handling. Visual Abstract: Abstract : Background: Gitelman syndrome is the most frequent hereditary salt-losing tubulopathy characterized by hypokalemic alkalosis and hypomagnesemia. Gitelman syndrome is caused by biallelic pathogenic variants in SLC12A3, encoding the Na + -Cl − cotransporter (NCC) expressed in the distal convoluted tubule. Pathogenic variants of CLCNKB, HNF1B, FXYD2, or KCNJ10 may result in the same renal phenotype of Gitelman syndrome, as they can lead to reduced NCC activity. For approximately 10 percent of patients with a Gitelman syndrome phenotype, the genotype is unknown. Methods: We identified mitochondrial DNA (mtDNA) variants in three families with Gitelman-like electrolyte abnormalities, then investigated 156 families for variants in MT-TI and MT-TF, which encode the transfer RNAs for phenylalanine and isoleucine. Mitochondrial respiratory chain function was assessed in patient fibroblasts. Mitochondrial dysfunction was induced in NCC-expressing HEK293 cells to assess the effect on thiazide-sensitive 22 Na + transport. Results: Genetic investigations revealed four mtDNA variants in 13 families: m.591C>T ( n =7), m.616T>C ( n =1), m.643A>G ( n =1) (all in MT-TF ), and m.4291T>C ( n =4, in MT-TI ). Variants were near homoplasmic in affected individuals. All variants were classified as pathogenic, except for m.643A>G, which was classified as a variant of uncertain significance. Importantly, affected members of six families with an MT-TF variant additionally suffered from progressive chronic kidney disease. Dysfunction of oxidative phosphorylation complex IV and reduced maximal mitochondrial respiratory capacity were found in patient fibroblasts. In vitro pharmacological inhibition of complex IV, mimicking the effect of the mtDNA variants, inhibited NCC phosphorylation and NCC-mediated sodium uptake. Conclusion: Pathogenic mtDNA variants in MT-TF and MT-TI can cause a Gitelman-like syndrome. Genetic investigation of mtDNA should be considered in patients with unexplained Gitelman syndrome-like tubulopathies.